2008
DOI: 10.1136/bmj.a257
|View full text |Cite
|
Sign up to set email alerts
|

Role of co-trimoxazole prophylaxis in reducing mortality in HIV infected adults being treated for tuberculosis: randomised clinical trial

Abstract: Objective To assess the impact of prophylactic oral cotrimoxazole in reducing mortality in HIV positive Zambian adults being treated for pulmonary tuberculosis. Design Double blind placebo controlled randomised clinical trial. Participants Two groups of antiretroviral treatment naive adults with HIV infection: patients newly diagnosed as having tuberculosis and receiving tuberculosis treatment either for the first time or for retreatment after relapse; previously treated patients not receiving treatment. Inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
61
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(65 citation statements)
references
References 18 publications
3
61
1
Order By: Relevance
“…15,17 Combination antiretroviral therapy (ART) in HIV-infected adults and children also reduces risk of diarrhea and enteric infection. 13,14,18 However, it is estimated that only 34% of 28.3 million HIV-infected individuals globally currently receive ART. 19 Water filtration devices reduce waterborne pathogens and subsequent diarrheal illness without contributing to antibiotic selective pressure or requiring clinic visits, and they can be used at any CD4 count.…”
Section: Introductionmentioning
confidence: 99%
“…15,17 Combination antiretroviral therapy (ART) in HIV-infected adults and children also reduces risk of diarrhea and enteric infection. 13,14,18 However, it is estimated that only 34% of 28.3 million HIV-infected individuals globally currently receive ART. 19 Water filtration devices reduce waterborne pathogens and subsequent diarrheal illness without contributing to antibiotic selective pressure or requiring clinic visits, and they can be used at any CD4 count.…”
Section: Introductionmentioning
confidence: 99%
“…11 Randomized trials that included ART-naĂŻve Africans found that cotrimoxazole improved survival while reducing the risk of malaria, pneumonia, sepsis, isosporiasis, T. gondii encephalitis, wasting and Kaposi's sarcoma. [12][13][14] However, a Senegalese trial that used half the recommended adult cotrimoxazole dose reported no mortality benefit in ART-naĂŻve adults. 15 A study in Uganda showed that treating HIV-infected adults with cotrimoxazole and ART reduced mortality in their uninfected children and the number of orphans.…”
mentioning
confidence: 99%
“…The value of co-trimoxazole in reducing the morbidity and mortality associated with HIV infection has been well established through clinical trials conducted in industrialized 5,6 and developing countries. [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26] CTXp is associated with a 25-46% reduction in mortality among individuals infected with HIV in sub-Saharan Africa, even in areas with high bacterial resistance to the antibiotic. These improvements in survival have been accompanied by substantial reductions in severe disease events and in the number of hospital admissions linked to invasive bacterial disease, pneumonia, malaria and diarrhoea.…”
Section: Introductionmentioning
confidence: 99%